2019
DOI: 10.1055/a-0808-2551
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends of Head Injuries Over Multiple Seasons in Professional Male Football (Soccer)

Abstract: The present study aimed to investigate time trends of head injuries and their injury mechanisms since a rule change as monitoring may help to identify causes of head injuries and may advance head injury prevention efforts. Based on continuously recorded data from the German football magazine “kicker Sportmagazin ® ” as well as other media sources, a database of head injuries in the 1 st German male Bundesliga was generated comprising 11 seasons (2006/07–2016/17). Injury mechanisms were analysed from video reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 39 publications
7
36
0
Order By: Relevance
“…The high frequency of reported injuries (64.3%) in a short period of time (2 years) indicates that even in collective sports, a high risk of these types of orofacial injuries is observed and this information is also confirmed by other studies, emphasizing the importance and necessity of educational and preventive measures and actions, aiming at maintaining the athlete's health (17)(18)(19). Orofacial lesions may occur at different levels of severity and may lead to esthetic, functional, psychological problems, and important economic impact since eventually the treatment for these types of accidents occurs in the medium and long term (19).…”
Section: Discussionsupporting
confidence: 53%
“…The high frequency of reported injuries (64.3%) in a short period of time (2 years) indicates that even in collective sports, a high risk of these types of orofacial injuries is observed and this information is also confirmed by other studies, emphasizing the importance and necessity of educational and preventive measures and actions, aiming at maintaining the athlete's health (17)(18)(19). Orofacial lesions may occur at different levels of severity and may lead to esthetic, functional, psychological problems, and important economic impact since eventually the treatment for these types of accidents occurs in the medium and long term (19).…”
Section: Discussionsupporting
confidence: 53%
“…Thus, we observed no gender differences in contrast to previous studies. One recent 2006-2016 German study found that the soccer concussion incidence slightly increased over time, 24 in contrast to the total number of head injuries and the overall injury incidence that have remained constant over time. 25 Future studies need to use a clear definition of a soccer-related concussion to determine whether the concussion risk in elite soccer is increasing, Accordingly, we used the definition from the 2012 Zurich consensus conference.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown in adults' football that heading duels are particularly key in the occurrence of head injury. [47][48][49] Therefore, header duels and unintentionally getting hit by a ball can be considered to be more likely accompanied by (head injury) consequences. 50,51 It is tempting to assume that the contact force between the ball and the player's head is an important consideration for head injury risk.…”
Section: Head Injuries In Match Play and Training Sessionsmentioning
confidence: 99%